The Sage handbook of global policing - Bradford, Ben; Jauregui, Beatrice; Loader, Ian; Steinberg, Jonny (Sage reference, 2016)
"The SAGE Handbook of Global Policing examines and critically retraces the field of policing studies by posing and exploring a series of fundamental questions to do with the concept and institutions of policing and their relation to social and political life in today's globalized world."-- Amazon.com website